Nutritional quality of spray dried protein hydrolysate from Black Tilapia (Oreochromis mossambicus) - Abdul-Hamid, Azizah; Bakar, Jamilah; Bee, Gan Hock (Elsevier Science, 2002)
The nutritional quality of spray-dried protein hydrolysate from black tilapia, a fresh water fish, was evaluated. Hydrolysed protein from Oreochromis mossambicus was spray-dried at two different temperatures of 150°C/76°C (inlet/outlet temp) and 180°C/90°C. Proximate analyses revealed that the dried hydrolysates consisted of 37.7-49.6% protein, 2.6-2.8% fat, 1.6-4.0% moisture and 8.6-8.7% ash. The higher drying temperature used was found to significantly decrease the contents of all amino acids analysed. Nevertheless, the protein quality of both dried hydrolysates was found to be high, with in vitro digestibilities of 88.4 and 92% and protein digestibility corrected amino acid scores of 0.34 and 0.82, respectively. In addition, the predicted protein efficiency ratios of the dried hydrolysates were calculated to be 2.97 and 2.53.